The body politics of successful ageing in the nexus of health, well-being and energy consumption practices. (February 2022) - Gordon, Ross; Harada, Theresa; Spotswood, Fiona
Abstract: In this paper, we introduce the idea of the bio-socio-material body to think through the body politics that emerge within the nexus of health, well-being and domestic energy consumption as people age. Our work draws upon an ethnographic study with older Australians in regional New South Wales, Australia. We enrich social practice theory conceptualisations by foregrounding the body as a dynamic bio-socio-material entity that shapes and is shaped by practices. In doing so, we draw attention to the body politics of managing health, well-being and energy consumption while trying to age successfully. We identify that the bio-socio-material dimensions of the body play an important role in how health, well-being and energy practices are performed. Energy practices are bound up in understandings of health and well-being as an ongoing and contingent process. Here, the use of energy and appliances becomes integral to how people negotiate and work towards successful ageing. We found that embodied practices of health, well-being and energy consumption are linked to biological, emotional, affective, social and material concerns that create body politics. These include tensions and challenges relating to health and vitality, caring for the sick and the dying, maintaining good mental health, the affordances of buildings and appliances, energy affordability and billing anxiety, social connectedness, and pleasures and pains. We raise questions emerging from our research on the implications for successful ageing. We call for attention to how health, well-being and energy are imbricated and for policy and programmes that better support older people to navigate the nexus of health, well-being and energy consumption as they age. Highlights: Energy consumption helps support health and well-being as people age. Bodily capacities mediate older people's energy, health and well-being practices. Participants navigate challenges managing health, well-being and energy consumption. Biological, emotional, affective, social and material concerns create a body politics. Policy should support health, well-being and energy practices for successful ageing.